Pembentukan Program Dana Pensiun Manfaat Pasti dengan Metode Benefit Prorate Constant Percent - Yulia Rahmawati. Z; Silvia Rosita (Jurnal Multidisiplin Madani, 2022)
Every employee is entitled to a future guarantee after the end of the working period. This study aims to establish a defined benefit pension plan which shows whether the age at work and the age at entering the pension plan affect pension benefits and contributions. This research is a literature study using case studies from secondary data of employer pension fund programs at PT. PLN West Kalimantan Region. The results obtained from this study include: 1) the greater the age to enter the pension fund program, the higher the contribution to be paid each year based on the age at which a person enters the partnership, and 2) the greater the age at which a person enters work, the benefits he receives. will be smaller based on participants with different working age and entry age into the same pension plan.